The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/ijc.34134
|View full text |Cite
|
Sign up to set email alerts
|

The oxidized‐LDL/LOX‐1 axis in tumor endothelial cells enhances metastasis by recruiting neutrophils and cancer cells

Abstract: Epidemiological relationships between cancer and cardiovascular diseases have been reported, but a molecular basis remains unclear. Some proteoglycans that strongly bind low‐density‐lipoprotein (LDL) are abundant both in atherosclerotic regions and in high metastatic‐tumor tissue. LDL retention is crucial for the initiation of atherosclerosis, although its contribution to malignancy of cancer is not known. In our study, we show the importance of the accumulation of LDL in tumor metastasis. We demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Additionally, studies proved that both DU145 (Sangrajrang et al, 1998 ; Edmondson et al, 2016 ) and MDA468 (Jones et al, 2014 ; Ibrahim et al, 2018 ) cell lines express tubulin protein. Furthermore, research studies showed that LDL-receptors are highly expressed in cancer cells more than in healthy cells (Song et al, 2009 ; Alhadad et al, 2020 ; Jaragh Alhadad, 2021 ) and induce cancer cell proliferation (Antalis et al, 2010 ; Gallagher et al, 2017 ), metastasis, and angiogenesis (Lu et al, 2017 ; Zhang et al, 2021 ; Tsumita et al, 2022 ). Based on that, pyrimidine heterocyclic anticancer agents were tested for the cytotoxicity effects with 48 hr.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies proved that both DU145 (Sangrajrang et al, 1998 ; Edmondson et al, 2016 ) and MDA468 (Jones et al, 2014 ; Ibrahim et al, 2018 ) cell lines express tubulin protein. Furthermore, research studies showed that LDL-receptors are highly expressed in cancer cells more than in healthy cells (Song et al, 2009 ; Alhadad et al, 2020 ; Jaragh Alhadad, 2021 ) and induce cancer cell proliferation (Antalis et al, 2010 ; Gallagher et al, 2017 ), metastasis, and angiogenesis (Lu et al, 2017 ; Zhang et al, 2021 ; Tsumita et al, 2022 ). Based on that, pyrimidine heterocyclic anticancer agents were tested for the cytotoxicity effects with 48 hr.…”
Section: Resultsmentioning
confidence: 99%
“…Third, our anticancer agents’ sizes were proved to be in the nano levels based on zeta data and scanning electron microscope data proved their morphologies. Agents’ morphology disrupts the microtubule's stability (Tsumita et al, 2022 ) and the nano-size particles increase the cellular uptake. A study, stated that rode shape anticancer agents increase the cellular uptake in-vitro and stimulate anticancer activity in-vivo (Xiupeng et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor endothelial cells (TECs) and normal endothelial cells (NECs) were isolated as previously reported [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tumor cell migration toward the S. mutans ‐stimulated ECs was assessed using transwell chambers (Corning, Life Sciences) as described previously, 20 , 22 , 23 with some modifications. Briefly, MS1 suspensions were placed into the lower compartment.…”
Section: Methodsmentioning
confidence: 99%